Da memória dos trabalhadores à memória da Petrobras: a história de um projeto - Figueiredo, Miriam Beatriz Collares (2009)
As a reflection of a worldwide movement where the memory has become a figure in contemporary societies, companies are also investing in the organization and preservation of their memories. We examined how the history of business has been organized based on the experience of the program Memory Petrobras. Over 6 years the company has implemented a series of initiatives aimed at recovering the historical landmarks of the company, ordering of data, collection of evidence material to its disclosure in a virtual museum. We discuss the relevance of this proposal in conjunction with other similar initiatives within the history of business.